Influence of random point defects introduced by proton irradiation on the flux creep rates and magnetic field dependence of the critical current density Jc of co-evaporated GdBa2Cu3O7−δ coated conductors - Haberkorn, N.; Jeehoon, Kim; Suárez, S; Lee, Jae-Hun; Moon, S.H.; Haberkorn, Néstor (IOP Publishing, 2015)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina